Praktik Jual Beli Hewan yang Sedang Mengandung di Pasar Sapi Nganjuk Menurut Persepektif Hukum Islam - Indah Purbasari; Takbir Wahyudi (Journal of Islamic Civilization, 2020)
This research aims to clarify the practice of sale and purchase agreement of pregnant livestock in Market livestock Nganjuk Regency based on the Islamic law perspective. The central issue of this research concerns the exsistence of an additional payment after delivery.  This research used the normative legal research method, with a statutory approach and supported by an analytical qualitative research approach. This study found that the practice of sale is unlawful regarding to Islamic law because of uncertainty in the consented price and forbidden object in syariah namely livestock in the womb. However, this transaction has not accomodated yet in Indonesian laws eventhough there is possibility of dispute among parties. Therefore, this research recommends that the statutes in the field of Islamic commercial law enables to cover the common transaction in society and not limited for Islamic financial institution in order to give protection due to shari’ah.